NEW DIRECTIONS OF REGULATION OF ENTREPRENEURSHIP DEVELOPMENT IN THE NEW UZBEKISTAN - Khojalepesov Polat Zinatdinovich; Sarsenbaev Ilhambay Eliwbay ugli, Madetova Nilufar Maxkamjan qizi (American Journals Publishing, 2022)
The article describes the incentives for accelerating business activities in New Uzbekistan. The article talks about the decrees and decisions adopted on the removal of bureaucratic obstacles, such as mandatory implementation of the activities of entrepreneurs in our Republic, and new opportunities being created.
Keywords: entrepreneurship, activity, barriers, mandatory, relief, business entity, report, decree, decision, regulation